2013
DOI: 10.1590/s0100-06832013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Doses de gesso em cafeeiro: influência nos teores de cálcio, magnésio, potássio e ph na solução de um latossolo vermelho distrófico

Abstract: Renée Coscione (8) RESUMOO desbalanço entre Ca 2+ , Mg 2+ e K + no solo como consequência das aplicações elevadas de gesso deve-se às relações de tamanho (raio iônico) e densidades de cargas (relação carga/raio) de cada espécie iônica. Quanto maior a densidade de carga, mais intensa será a ligação iônica do cátion com íons de cargas opostas como OH -e SO 4 -2 . Dessa maneira, o uso excessivo de gesso agrícola, sem considerar o balanço de cargas das partículas do solo; o equilíbrio iônico; e a CTC podem resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 24 publications
3
37
0
12
Order By: Relevance
“…This product is a good source of exchangeable calcium (Ca 2+ ), which under the dry climate conditions in Alto São Francisco, as shown by Ramos et al (2013) in studies of chemical speciation, promote a slow release of this nutrient, but leading to relevant levels (27 mmol c dm -3 ) to promote clay flocculation and aggregate area increase, improving soil aggregation (CREMON et al, 2009;SOUZA et al, 2012). To confirm the Ca 2+ contribution in soil aggregation, Silva et al (2013) observed increased geometric diameter of aggregates in experimental areas of Latosols (Oxisols) that had received high doses of agricultural gypsum (7 and 28 Mg ha -1 ), whose sorptive complex had about 50 mmol dm -3 of Ca…”
Section: Resultsmentioning
confidence: 99%
“…This product is a good source of exchangeable calcium (Ca 2+ ), which under the dry climate conditions in Alto São Francisco, as shown by Ramos et al (2013) in studies of chemical speciation, promote a slow release of this nutrient, but leading to relevant levels (27 mmol c dm -3 ) to promote clay flocculation and aggregate area increase, improving soil aggregation (CREMON et al, 2009;SOUZA et al, 2012). To confirm the Ca 2+ contribution in soil aggregation, Silva et al (2013) observed increased geometric diameter of aggregates in experimental areas of Latosols (Oxisols) that had received high doses of agricultural gypsum (7 and 28 Mg ha -1 ), whose sorptive complex had about 50 mmol dm -3 of Ca…”
Section: Resultsmentioning
confidence: 99%
“…In G-0, although no additional gypsum was applied to supply Ca for plant nutrition, calcium nitrate (105 kg ha -1 ) was used to maintain adequate to high soil Ca 2+ levels (Ramos et al, 2013), explaining the very stable aggregates observed in this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, at a depth of 0.20 m, there was a reservoir of gypsum, which, due to dry conditions in the Upper São Francisco region, underwent slow dissolution and gradually released Ca 2+ to the soil at appropriate levels (27 mmol c dm -3 ). This initiated the clay flocculation process, and promoted soil aggregation improvements (Cremon et al, 2009;Ramos et al, 2013;Silva et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…After 2.5 years was 27 and50 mmol c dm -3 in G0 and G7, respectively, and in G28 was 48 mmol c dm -3 (Silva et al 2013;Ramos et al 2013). In G7 quantities are insufficient to act as an aggregate dispersing agent (Spera et al 2008;Cremon et al 2009).…”
Section: Treatmentsmentioning
confidence: 97%